2018
DOI: 10.3390/ma11061036
|View full text |Cite
|
Sign up to set email alerts
|

Single Step Laser Transfer and Laser Curing of Ag NanoWires: A Digital Process for the Fabrication of Flexible and Transparent Microelectrodes

Abstract: Ag nanowire (NW) networks have exquisite optical and electrical properties which make them ideal candidate materials for flexible transparent conductive electrodes. Despite the compatibility of Ag NW networks with laser processing, few demonstrations of laser fabricated Ag NW based components currently exist. In this work, we report on a novel single step laser transferring and laser curing process of micrometer sized pixels of Ag NW networks on flexible substrates. This process relies on the selective laser h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…The middle and right panels of 8,57 drop coating, 30 spin coating, 32 spray coating, 43 and Mayer rod coating 13,31 ) and one-step printing methods (ground color of purple) (electrohydrodynamic printing, 49 additive printing, 58 screen printing, 25 inkjet printing, 34 and seed particle printing 59 ), as well as some other transparent conductors (ground color of green) through direct writing of silver nanoparticles (Ag NPs), 60 copper random network, 61 direct printing of Ag precursors, 50 and laser transferring. 51 Note: For the printed Ag NW patterns in the literature, where the transmittance values at the wavelength of 550 nm are not clearly mentioned, the FoMs have been estimated based on the film thicknesses and the physical appearance of the patterns in comparison to our work. b Schematics for the process to achieve high transparency and conductivity for the printed Ag NW films in this work.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…The middle and right panels of 8,57 drop coating, 30 spin coating, 32 spray coating, 43 and Mayer rod coating 13,31 ) and one-step printing methods (ground color of purple) (electrohydrodynamic printing, 49 additive printing, 58 screen printing, 25 inkjet printing, 34 and seed particle printing 59 ), as well as some other transparent conductors (ground color of green) through direct writing of silver nanoparticles (Ag NPs), 60 copper random network, 61 direct printing of Ag precursors, 50 and laser transferring. 51 Note: For the printed Ag NW patterns in the literature, where the transmittance values at the wavelength of 550 nm are not clearly mentioned, the FoMs have been estimated based on the film thicknesses and the physical appearance of the patterns in comparison to our work. b Schematics for the process to achieve high transparency and conductivity for the printed Ag NW films in this work.…”
Section: Resultsmentioning
confidence: 93%
“…For comparison's sake, other studies have reported the following sheet resistance and transmittance values: screen-printed Ag NW patterns (calculated sheet resistance, 1.05 ohm/sq; no transparency data), 25 gravureprinted Ag NW patterns (calculated sheet resistance, 0.468 ohm/ sq; no transparency data), 48 electrohydrodynamic printed Ag NW patterns (sheet resistance, 1.5-3.7 ohm/sq; no transparency data), 49 direct printing of Ag precursor (sheet resistance, 27.6 ohm/sq; transmittance: 94.7%), 50 and laser transferred Ag NW patterns (sheet resistance, 59.1 ohm/sq; transmittance: 92.3%). 51 To further highlight the influence of laser sintering on the properties of transparent patterns, we calculated and plotted the FoM of the printed Ag NW patterns before and after laser sintering, as illustrated in Fig. 3b.…”
Section: Resultsmentioning
confidence: 99%
“…7b. Zacharatos et al have also recently shown the use of LIFT for AgNW electrodes (Zacharatos et al 2018). In this work, AgNW suspensions are transferred directly in the solid phase under low vacuum onto the receiving substrate without the use of a sacrificial layer.…”
Section: Transparent Conductive Electrodesmentioning
confidence: 97%
“…After the laser printing process is over, a sintering process is required so that the copper ink patterns obtain the desired electrical properties. In this work we have employed laser sintering for selective and high resolution heating of the nanoparticles, as it is extensively described in previous works [9][10][11]. First the printed ink dries in ambient atmosphere for a few minutes at room temperature, then the sintering procedure takes place with the direct exposure of the pattern to the laser beam ( Fig.…”
Section: Lift and Laser Sintering: Process And Setupmentioning
confidence: 99%
“…One of the most widely used additive micro-manufacturing technologies relies on the direct printing followed by selective sintering of metal nanoparticle inks. Laser printing relying on the Laser Induced Forward Transfer (LIFT) technique, combined with selective laser sintering stand out among the additive micro-manufacturing technologies [3][4][5] owing to the high speed (>1 m/s) and high resolution (<50 µm) [6], as well as the lateral selectivity and minimized heat affected zone with demonstrations of highly conductive micro-patterns in flexible electronic applications [7][8][9][10][11]. In this technology, inks comprising metals like gold and silver have been primarily employed due to their high conductivity and environmental stability [12].…”
Section: Introductionmentioning
confidence: 99%